MECHANICAL ENGINEERING STUDENTâ€™S PERCEPTION OFFOUR TEACHER COMPETENCES: PEDAGOGICAL, PERSONALITY, SOCIAL, AND PROFESSIONAL COMPETENCES - Najmuddin, Muhammad Guruh; Suherman, Amay; Hamdani, Aam (Journal of Mechanical Engineering Education, 2020)
Aim of this study is to determine in wich category the studentâ€™s perception about pedagogical competence, personality competence, sosial competence, and professional competence. This study is using quantitative descriptive method. The sample of this study is students who have completed the 6thsemester with total 58 samples. This study using closed question that distribute to the samples. The result of this study is that studentsâ€™ perception about pedagogical competence are in the very good category, studentsâ€™ perception about personality competence are in the very good category, studentsâ€™ perception about social competence are in the very good category, studentsâ€™ perception about proffesional competence are in the very good category.There are 53 (91,4%) students that have aâ€œVery Goodâ€ category in perception ofpedagogical competences.There are 38 (65,5%) students that have a â€œVery Goodâ€ category in perception of personality competences.There are 43 (74,1%) students that have a â€œVery Goodâ€ category in perception of socialcompetences.There are 35(60,3%) students that have a â€œVery Goodâ€ category in perception of professionalcompetences.Studentsâ€™ perception of four teacher competences are in very good category, it mean that studentsâ€™ quality are in a good category.